La symbolique des lieux urbains en France lors des attentats de janvier 2015 - Charles-Edouard Houllier-Guibert (EchoGéo)
The "Je suis Charlie" phenomenon is explored by examining photographs used by the mass media in France and all around the world, in January 2015. The capacity of journalists to show symbolic monuments of each city is shown. These pictures allowed a transformation of public space into a symbolic area with an identifying monument. Among public places in France, the place de la République in Paris has been one of the most important symbolic areas over the past months. We can see the creation of a kind of memorial in this square where no attacks occurred but there were the largest gatherings for many years.